2013
DOI: 10.1007/978-3-642-41068-0_6
|View full text |Cite
|
Sign up to set email alerts
|

Multi-command Tactile Brain Computer Interface: A Feasibility Study

Abstract: The study presented explores the extent to which tactile stimuli delivered to the ten digits of a BCI-naive subject can serve as a platform for a brain computer interface (BCI) that could be used in an interactive application such as robotic vehicle operation. The ten fingertips are used to evoke somatosensory brain responses, thus defining a tactile brain computer interface (tBCI). Experimental results on subjects performing online (real-time) tBCI, using stimuli with a moderately fast inter-stimulus-interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…The proposal is similar to the previously reported waist positions based tBCI reported in [1] with a difference that we propose to use the chest area simulation which simplifies a vehicular robot operation in comparison to our previous handand head-stimulus-based tBCI solutions reported in [10,9].…”
Section: Introductionsupporting
confidence: 76%
“…The proposal is similar to the previously reported waist positions based tBCI reported in [1] with a difference that we propose to use the chest area simulation which simplifies a vehicular robot operation in comparison to our previous handand head-stimulus-based tBCI solutions reported in [10,9].…”
Section: Introductionsupporting
confidence: 76%
“…This research project was an improvement of a previously reported finger stimulus tactile BCI developed also by the BCI–lab research group (Mori et al, 2013b). The direct brain–robotics interface was based on the P300 response (Donchin and Coles, 1988) classification in a tactile sensory modality (Brouwer and Van Erp, 2010).…”
Section: Resultsmentioning
confidence: 95%
“…The AUTD stimulus generator in the RautdBCI experiments delivered tactile and contactless stimuli to the user skin only via air pressure modulation using a technique of beam-forming-based focused ultrasound (Iwamoto et al, 2008; Mori et al, 2012, 2013a,b,c,d; Hamada, 2014). The AUTD stimulation effect was achieved due to a generated ultrasonic radiation static force, which was produced by an intense sound pressure amplitude.…”
Section: Resultsmentioning
confidence: 99%
“…BCI prototypes described included a tactile-based BCI involving tactors to deliver P300 generating stimuli [156], and finger/hand [157, 158] and head/bone-conduction [159, 160] based tactile BCI prototypes.…”
Section: Future Bci Directionsmentioning
confidence: 99%